Circulation of Judgments in the EU and Public Policy: A Recent Decision of the Italian Supreme Court - Fossati, Curzio (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The Italian Court of Cassation recently ruled on the compatibility with Italian public policy of the recognition of a Danish judgment ordering an Italian company to pay a fine for violations of employment law. The judgment raises several issues relating to the refusal ground in question, in particular its applicability where the court of origin of the decision fails to comply with its obligation to refer the case to the Court of Justice and where the judgment imposes punitive damages. The decision offers the opportunity to make some considerations on the evolution of the concept of public policy in the context of the circulation of judgments within the European Union.
Keywords: Regulation (EU) No 1215/2012 (Brussels I-bis); recognition and enforcement of foreign judgments; refusal grounds; public policy; possibility to raise the refusal ground ex officio; obligation to make a reference to the Court of Justice; punitive damages